2017
DOI: 10.7554/elife.22848
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 in AGRP neurons integrates exteroceptive and interoceptive food-related cues in the modulation of adaptive energy expenditure in mice

Abstract: Energy dissipation through interscapular brown adipose tissue (iBAT) thermogenesis is an important contributor to adaptive energy expenditure. However, it remains unresolved how acute and chronic changes in energy availability are detected by the brain to adjust iBAT activity and maintain energy homeostasis. Here, we provide evidence that AGRP inhibitory tone to iBAT represents an energy-sparing circuit that integrates environmental food cues and internal signals of energy availability. We establish a role for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…They are activated upon fasting, inhibited upon refeeding as well as transiently and rapidly inhibited during the sensory perception of food 2 . Here, sensory food perception-dependent regulation of AgRP neurons controls BAT thermogenesis 22 . Interestingly, the ability of sensory food perception to simultaneously activate POMC neurons has been linked to prime liver ER-homeostasis for the postprandial state, in line with the general concept, that melanocortin neurons adapt multiple physiological processes in accordance to anticipated or actual changes in the energy state of the organism 23 .…”
Section: Discussionmentioning
confidence: 99%
“…They are activated upon fasting, inhibited upon refeeding as well as transiently and rapidly inhibited during the sensory perception of food 2 . Here, sensory food perception-dependent regulation of AgRP neurons controls BAT thermogenesis 22 . Interestingly, the ability of sensory food perception to simultaneously activate POMC neurons has been linked to prime liver ER-homeostasis for the postprandial state, in line with the general concept, that melanocortin neurons adapt multiple physiological processes in accordance to anticipated or actual changes in the energy state of the organism 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of S6K protects high fat feeding induced hyperphagia, fat accumulation and insulin resistance suggesting a critical role of MBH S6K activity in energy homeostasis [ 75 ]. Constitutive activation of mTORC1 signaling in the AgRP neurons modulates sympathetic tone to increase BAT thermogenesis and energy expenditure and protects against diet-induced obesity [ 76 ]. However, a recent study has shown that specific ablation of S6K1 in POMC or AgRP neurons causes no significant change in food intake and body weight.…”
Section: Mtor Signaling In Brainmentioning
confidence: 99%
“…Thus, the signaling molecules of the hypothalamic arcuate nucleus support the search for food, rather than eating (Ammar et al, 2000; Nergårdh et al, 2007; Chen et al, 2015; Dietrich et al, 2015; Burnett et al, 2016). The agouti-related protein neurons of this nucleus can monitor the availability of food in the environment, changing energy utilization from fat to carbohydrate (Chen et al, 2015; Burke et al, 2017; Cavalcanti-de-Albuquerque et al, 2019). Silencing these neurons eliminates the search for food but leaves chewing and swallowing unaffected (Thomas et al, 2018), replicating the effect of dopamine receptor blockade or depletion (Berridge et al, 1989; Bednar et al, 1992; Qian et al, 1998).…”
Section: The Evolutionary Perspectivementioning
confidence: 99%